2018
DOI: 10.1021/acs.energyfuels.8b01316
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influence Factors of Leaching of Rare Earth Elements from Coal Fly Ash

Abstract: Rare earth elements (REEs) are very important strategic resources, but the traditional high-quality rare earth resources are becoming increasingly scarce. Coal fly ash (CFA) in some areas in the world has a high REE content, which can be a potential supplement to the rare earth resources. CFA samples collected from the Panbei Power Plant in Guizhou Province of China, in which the REE content is 489 ppm, was used as the research object in this study. Taking three REEs (lanthanum (La), cerium (Ce), and neodymium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 34 publications
(46 reference statements)
4
47
0
Order By: Relevance
“…Many studies have been published in recent years focused on the chemical extraction of REEs from coal combustion ashes [26,53,76,88,89,[91][92][93][94][95][96][97][98][99][100][101]. As shown in Table 4, acid leaching has been extensively exploited to extract REEs from coal combustion ash, and often the ash materials must be chemically and/or thermally treated prior to acid leaching to achieve better extraction performance.…”
Section: Chemical Extraction Of Rees From Coal Combustion Ashmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have been published in recent years focused on the chemical extraction of REEs from coal combustion ashes [26,53,76,88,89,[91][92][93][94][95][96][97][98][99][100][101]. As shown in Table 4, acid leaching has been extensively exploited to extract REEs from coal combustion ash, and often the ash materials must be chemically and/or thermally treated prior to acid leaching to achieve better extraction performance.…”
Section: Chemical Extraction Of Rees From Coal Combustion Ashmentioning
confidence: 99%
“…Nearly 100% recovery was obtained from the samples using 12 M HCl at 85 • C, and a considerable amount of REEs (71%) were extracted from a fly ash sample of the same source even under much weaker acidity (1 M HCl). Cao et al conducted a parametric study to optimize the leaching recovery of REEs from a fly ash sample that was collected from a power plant located in Guizhou, China [91]. It was found that 71.9% of La, 66.0% of Ce, and 61.9% of Nd were leached using 3 M HCl at 60 • C. However, due to the fact that most of the REEs are encapsulated in the amorphous structures of fly ash generated by combusting pulverized coal under high temperature (~1400 • C), relatively low recoveries were usually achieved using acid leaching alone.…”
Section: Acid Leaching Of Rees From Coal Combustion Ashesmentioning
confidence: 99%
See 2 more Smart Citations
“…are some studies which use coal ash to recover metals by different methods. Cao et al studied the recovery of REEs and found recoveries of the three metals La, Ce, and Nd of 71.9 %, 66 %, and 61.9 %, respectively [21]. Tuan et al used acid leaching to recover rare elements such as Y, Nd, and Dy from coal ash.…”
Section: Introductionmentioning
confidence: 99%